Superoxide dismutase (SOD) activity of Ceriops zippeliana in Segara Anakan Cilacap (Indonesia) under heavy metal accumulation (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sukmarani D, Proklamasiningsih E, Susanto AH, Ardli ER, SudianaE, Yani E. 2021. Superoxide dismutase (SOD) activity of Ceriops zippelianaBlume in Segara Anakan Cilacap (Indonesia) under heavy metal accumulation. Biodiversitas 22:5627-5635. Ceriops zippeliana Blumeis a true mangrove species that occupy habitats exposed to environmental stress, such as salinity and heavy metal contamination, which is the case in Segara Anakan Cilacap, Central Java. Both salinity and heavy metal stress can lead to the production of reactive oxygen species (ROS), which can be detrimental to plants if they are present in excess. Plants have defense mechanisms to prevent excessive ROS, one of which is by the use of superoxide dismutase (SOD) enzyme. This study aims to explain the accumulation of heavy metals (Pb, Cd, Cu, and Zn) in C. zippeliana as well as the translocation of the metals. In addition, the correlation between heavy metal concentrations and SOD activity in C. zippeliana is reported. Plant samples were randomly collected from Segara Anakan, Cilacap. The analysis was conducted using the bio-concentration factor (BCF), translocation factor (TF), and linear regression in the SPSS program. It was found that Pb, Cu, and Zn levels in Segara Anakan Cilacap sediments were still within acceptable limits, while Cd level was moderately polluting. Metal accumulation was higher in the branches of C. zippeliana compared to those in roots and leaves. The SOD activity of C. zippeliana in Segara Anakan is seemingly not related to metal contents in plant parts.